Acculturation and Self-Management Perceptions Among Mexican American Adults With Type 2 Diabetes. Issue 2 (April 2017) - Plasencia, Julie; Hoerr, Sharon; Carolan, Marsha; Weatherspoon, Lorraine
Abstract : Because type 2 diabetes (T2DM) is disproportionately high among Mexican Americans in the United States, this study examined how acculturation influences T2DM self-management, a critical component for disease outcome. Qualitative interviews of 24 low-income Mexican American patients with T2DM were matched to their biomedical and dietary data and degree of acculturation. Greater acculturation to the United States was associated with less favorable diabetes control, fiber density, leisure-time physical activity, and more physical disability. Health care professionals can improve their cultural competence by learning culturally appropriate foods and fostering a warm, caring manner with Mexican Americans to enhance their sense of well-being and compliance with T2DM recommendations.